Afiksasi, Reduplikasi, dan Abrevasi Bahasa Gaul pada Update Status Anggota Grub Facebook Komunitas Touring Indonesia (KTI) - Nasirudin Al Mustofa; Atiqa Sabardilla (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2022)
The use of language in society often has various modifications called slang. The spread of slang is fast in society, especially on social media Facebook. The purpose of this study was to examine the forms of affixation, reduplication, and slang abbreviations found in the status updates of members of the Indonesian Touring Community (KTI) facebook group. This study uses a qualitative descriptive method to view, analyze, and describe the data regarding the forms of affixation, reduplication, and slang abbreviations used. Data collection techniques use listening and note-taking techniques, while data analysis techniques use analytical techniques according to Miles and Huberman. This study uses the morphological process theory according to Kridalaksana which is based on the forms of affixation, reduplication, and abbreviation. The findings of this study, (1) members of the Indonesian Touring Community facebook group often use slang in their status updates, (2) the morphological processes of slang that often appear are affixation, reduplication, and abbreviation. From the results of the study, it can be said that affixation, reduplication, and slang abbreviations on status updates of members of the Indonesian Touring Community (KTI) facebook group aim to familiarize members of the community. In addition, forms of affixation, reduplication, and slang abbreviations are also used to facilitate written communication.